Penerapan Model NGOPI untuk Meningkatkan Kemampuan Membaca Pemahaman pada Penyelesaian Soal Cerita Matematika Siswa Kelas V - Octaviani Nusa; Henny Dewi Koeswanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading comprehension is a basic competency that plays an important role in helping students understand information and solve mathematical story problems. However, this ability is still relatively low so that students experience difficulties in identifying important information, determining solution strategies, and obtaining correct answers. This study aims to improve students' reading comprehension skills in solving mathematical story problems through the application of the NGOPI Model. This study contributes in the form of the application of the NGOPI Model as an alternative learning that integrates reading literacy activities and mathematical problem solving at the elementary school level. The study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which was carried out in two cycles, including the planning, action implementation, observation, and reflection stages. The research subjects were 27 fifth-grade students of SDN Kutowinangun 08 in the 2025/2026 academic year. Data were collected through observation, tests, documentation, and field notes, then analyzed using quantitative and qualitative descriptive techniques. The results showed that the application of the NGOPI Model was able to improve students' reading comprehension skills. The percentage of learning completion increased by 40.74%, namely from 48.15% in Cycle I to 88.89% in Cycle II, while the average value increased by 13.89 points, from 72.41 to 86.30. Improvements also occurred in all indicators of reading comprehension skills, including understanding the contents of story problems, identifying known and asked information, determining solution strategies, and solving story problems with correct answers. Thus, the NGOPI Model has been proven effective in improving students' reading comprehension skills in solving mathematical story problems, and can be used as an alternative learning model to strengthen reading literacy and problem-solving skills in elementary schools.